Tobacco cessation : a practice manual for primary care physicians - Panda, Rajmohan; Mathur, Manu Raj (Boca Raton : CRC Press, 2020)
"Cessation of tobacco use is the need of the hour given that it is the single largest cause of disease and premature death in the world. This book covers epidemiology and risks, user classification, nicotine replacement therapy, pharmacological aids, behavioral modification and patient counseling techniques, and personalized action plan development"--
Tobacco and health / Dr. Sandeep Mahapatra & Mr. Kumar Gaurav -- Theories of tobacco addiction / Dr. Sonu Goel -- Behavioral and psychological approaches for tobacco cessation / Dr. Sonali Jhanjhee -- Pharmacological approaches for tobacco cessations / Dr. Binod Patro & Dr. Suravii Patro -- How to develop a tobacco cessation centre? / Dr. Rana.J Singh -- Patient follow up / Dr. Vikrant Mohanty -- Evaluation of cessation practices / Dr. Rakesh Gupta.
OCLC-licensed vendor bibliographic record.
Keywords: Smoking cessation; MEDICAL / General; MEDICAL / Family & General Practice; MEDICAL / Public Health